2022
DOI: 10.11591/ijphs.v11i2.21372
|View full text |Cite
|
Sign up to set email alerts
|

Mattering, social support, resilience and sense of empowerment during the pandemic

Abstract: The sense of empowerment had always been reported as contingent upon resilience, the sense of financial security, and perceived social support (PSS). In the context of the Malaysian urban population, the outbreak shifted social dynamics through the enforcement of movement control order (MCO), a partial-to-full lockdown policy enforced by the government to curb the virus. Studies in the local context suggested that the implementation of MCO led to a sense of uncertainty towards social support and financial secu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It suggests that our self-esteem and sense of self-worth are influenced by our perception of how we are socially valued by others [11]. Sociometer theory was supported by many previous studies, such as the study by Nga et al [12] that reported higher sense of empowerment among individuals who believe that their social environment was supportive and inclusive. Contextually, it was also reported that sociometer, the sense that we are included in social circles and socially supported, played significant role in protecting college students from anxiety and depression The role of sociometer in the form of perceived social support (PSS), perceived social inclusion, and the sense of mattering was reported to be significant and positive towards mental health among college students, and their prevalence was reported to be similar between before, during, and after the pandemic outbreak [8], [13]- [15].…”
Section: Introductionmentioning
confidence: 82%
“…It suggests that our self-esteem and sense of self-worth are influenced by our perception of how we are socially valued by others [11]. Sociometer theory was supported by many previous studies, such as the study by Nga et al [12] that reported higher sense of empowerment among individuals who believe that their social environment was supportive and inclusive. Contextually, it was also reported that sociometer, the sense that we are included in social circles and socially supported, played significant role in protecting college students from anxiety and depression The role of sociometer in the form of perceived social support (PSS), perceived social inclusion, and the sense of mattering was reported to be significant and positive towards mental health among college students, and their prevalence was reported to be similar between before, during, and after the pandemic outbreak [8], [13]- [15].…”
Section: Introductionmentioning
confidence: 82%
“…It is important to note that the extreme sense of mattering within a marriage can led to negative outcomes, such as high demand of validation, attention, and perceived fairness, or an overwhelming sense of responsibility for every task in the household [17]. Additionally, the sense of mattering is influenced by various factors, including the perceived social support [18], [19]. Within a marital relationship, individuals are more likely to believe they matter to their spouse when they perceive that they are supported and treated fairly [20].…”
Section: Introductionmentioning
confidence: 99%
“…The mediation relationship between the sense of mattering and relationship satisfaction is moderated by secure attachment style, whereby individuals with low-to-moderate secure attachment style tend to be more satisfied with their relationship when they feel they matter enough to their spouses [16]. When attachment to one's spouse is secured, individuals tend to be more satisfied with their life, and in turn, more satisfied with their relationship (18). The sense of mattering is influenced by various factors, such as the perception of being supported one's spouse [18], [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation